The Influence of Overtourism and Tourism Preassure on Per-Capita Income in Bali - Khairani, Annisa Rizky; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2026)
This study investigates the impact of tourism pressure on economic welfare in Bali, measured by GRDP per capita. Tourism pressure is proxied by three indicators: the tourist-to-resident ratio, the tourist-to-accommodation ratio, and tourist density across destination areas. The analysis employs district/city panel data for the period 2017–2024 using a fixed-effects model, with the inclusion of a COVID-19 dummy variable. The results indicate that tourism pressure has a non-linear and jointly significant effect, explaining approximately 29.13% of the variation in GRDP per capita. The tourist to resident ratio exhibits an inverted U-shaped relationship, where its positive effect diminishes beyond a certain threshold. In contrast, tourist density follows a U-shaped pattern, where low density does not contribute significantly to welfare, while higher density is associated with improvements in GRDP per capita. The tourist-to-accommodation ratio is not statistically significant, suggesting that expanding accommodation capacity does not necessarily enhance economic welfare. The COVID-19 dummy is also insignificant, reflecting the uneven and gradual nature of the pandemic’s economic impact. These findings highlight the importance of managing tourism pressure in line with local carrying capacity while strengthening the retention of tourism-generated income within the local economy.